Disencounters in an architectural intervention in historic centers between object and heritage subjects. Case study: Church of Belen, Cusco - Peru (2019-2022) - Abarca-Ancori, Amparo; Hayakawa-Casas, José Carlos (Estoa. Journal of the Faculty of Architecture and Urbanism, 2025)
As long as the built heritage is not appropriated by the heritage subjects such as the population involved and the state, any architectural conservation intervention will be indifferent. Exposing the possibility of its transmission to future generations. This would lead to the extinction of the inherited culture; even worse, the loss of local identities. What factors lead to this undesirable scenario? Determining this is the objective of the research. Evaluating the criteria of architectural intervention in the Church of Bethlehem, located in the structuring area II of the Historic Center of Cusco in Peru, contrasting them with structured interviews to heritage subjects. The results show the hegemony of preserving the materiality of the monument, dissociated from the immateriality, from the attachments and interests of the heritage subjects and disintegrated from its context. Disencounter reflected in the absence of inter-institutional cooperation, holistic intervention and unprecedented exclusion of the heritage subjects before, during and after the architectural intervention process.